2015
DOI: 10.3390/buildings5031003
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Energy Implications of Downtown High-Rise vs. Suburban Low-Rise Living: An Overview and Quantitative Case Study for Chicago

Abstract: Abstract:It is commonly accepted that the concentration of people in high-density urban city centers, which are typically dominated by medium-and high-rise buildings located close to public transit systems, offers greater overall energy efficiency and lower life-cycle greenhouse gas emissions than lower-density expanded suburbs, which are dominated by low-rise single-family buildings and larger per-person automobile travel requirements. However, few studies have combined quantitative analyses of the life-cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Specifically, Perkins et al [7] used site energy instead of source energy, which could significantly lower their BOE value as well as the share of the total OE since electricity has a high primary energy conversion factor (typically~3). Further, our estimates of BOE as a fraction of total OE are similar to those reported in Fuller et al and Du et al [11,12].…”
Section: Comparison To Previous Studiessupporting
confidence: 90%
See 3 more Smart Citations
“…Specifically, Perkins et al [7] used site energy instead of source energy, which could significantly lower their BOE value as well as the share of the total OE since electricity has a high primary energy conversion factor (typically~3). Further, our estimates of BOE as a fraction of total OE are similar to those reported in Fuller et al and Du et al [11,12].…”
Section: Comparison To Previous Studiessupporting
confidence: 90%
“…This result is in conflict with some early studies such as Norman et al [3], Perkins et al [7], and Stephan et al [10], in which OE for urban high density living was found to be 55%, 24%, and 27% lower than in suburban low density living on a per-person basis, respectively. However, these results are generally in line with other studies such as Fuller et al and Du et al [11,12]. Fuller et al [11] found that city-center living consumed approximately 33% more than inner-suburban low-density living.…”
Section: Comparison To Previous Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…From the perspective of energy use and carbon emissions, there is generally support for higher density urban living [2][3][4][5][6][7][8][9][10]. At the same time, from a social perspective, there has been a long-standing argument that people living in dense urban cities may have a lower quality of life (QoL) and are less happy or less satisfied with their lives than those living in the suburbs, based on city and regional data sets [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%